2020
DOI: 10.1038/s41598-020-78466-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of highly active antiretroviral treatment on TB incidence among HIV infected children and their clinical profile, retrospective cohort study, South West Ethiopia

Abstract: Globally, 1.8 million HIV infected children live with HIV; nearly 53% of them were receiving HIV treatment. People who are infected with HIV are 18 times more likely to develop active TB. Despite antiretroviral treatment has shown marked reduction in TB incidence, TB continues to occur in Sub-Saharan countries including Ethiopia among HIV infected people. The effect of highly active antiretroviral treatment is quite successful in developed countries. However, in developing country TB/HIV co-infection remains p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 26 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…Evidence from other African settings also demonstrated the persistent risk of HIVassociated TB despite ART (Table 1). In a cohort of CALHIV in Ethiopia, ART only reduced the hazard ratio of TB by 36% [4]. The TB incidence rate was 7.7 per 100 person years (95% CI, 6.3-9.2) in CALHIV on ART, similar to 8.2 per 100 person years (95% CI 6.8-9.8) in ART naïve CALHIV.…”
Section: Emerging Epidemiology On Tb Risk and Outcomes In High-hiv/tb...mentioning
confidence: 84%
“…Evidence from other African settings also demonstrated the persistent risk of HIVassociated TB despite ART (Table 1). In a cohort of CALHIV in Ethiopia, ART only reduced the hazard ratio of TB by 36% [4]. The TB incidence rate was 7.7 per 100 person years (95% CI, 6.3-9.2) in CALHIV on ART, similar to 8.2 per 100 person years (95% CI 6.8-9.8) in ART naïve CALHIV.…”
Section: Emerging Epidemiology On Tb Risk and Outcomes In High-hiv/tb...mentioning
confidence: 84%
“… 8 Adults 3072 10,000 57 0.57 16. East Africa Tiruneh F, et al [ 78 ], 2020 Ethiopia Retr. 6 Children 800 2942.99 189 7.917 17.…”
Section: Resultsmentioning
confidence: 99%
“…The level of heterogeneity in all publication date categories was significantly high ( P < 0.001). In the subgroup analysis of the target population, four studies included in this systematic review and meta-analysis [ 59 , 78 , 95 , 99 ] were excluded from the subgroup analysis because their study populations did not have a distinct age group that differentiated children from adults. In children, the incidence rate of tuberculosis was 3.42 (95% CI: 1.78, 5.57) per 100 person-years, with significant heterogeneity (I 2 = 98.49%, p < 0.001), whereas in adults, the incidence rate was 3.79 (95% CI: 2.63, 5.15) per 100 person-years, with high heterogeneity (I 2 = 99.78%, p < 0.001) (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was proven that HAART increases the survival of HIV/ TB co-infected patients and reduces their mortality [7]. Studies of Alemu et al [8] and Tiruneh et al [9] confirmed that if HIV/AIDS patients take ART, it enables them to reduce the risk of developing active TB disease. WHO also recommends that all TB patients with HIV should be started on antiretroviral therapy (ART), irrespective of their CD4+ counts [10], and this survival time of patients was often studied by using non-parametric and parametric survival models, including Kaplan-Meier, Cox PH, and AFT models.…”
Section: Source Of Datamentioning
confidence: 98%